Does access to credit reduce SMEs' tax avoidance? Evidence from a regression discontinuity design - Xiaowei Kong; Deng-Kui Si; Haiyang Li; Dongmin Kong (Financial Innovation, 2021)
This study investigates the effect of targeted reserve requirement ratio cuts (TRRRCs) on tax avoidance among small and micro enterprises (SMEs) with operating revenues below specific cutoffs in China. Using a regression discontinuity design, we causally show that, by increasing loan availability, TRRRCs significantly alleviate the financial constraints and cash dependence of SMEs and consequently reduce tax avoidance. This is especially the case among firms with lower market power and higher entertainment and travel costs. Our findings provide evidence for the real effect of TRRRCs on corporate tax avoidance and show the inclusive effect of TRRRCs on SMEs. In doing so, we indirectly reveal a rent-seeking channel underlying bank lending, thus offering clear policy implications for regulators.
Keywords: E52; G32; H25; 650; Access to finance; Small and micro enterprises (SMEs); Targeted reserve requirement ratio cuts (TRRRCs); Tax avoidance